The Effect of Locavorism on Behavior Intention in The Scope of Goal-Directed Behavior Theory: Alaçati Herb Festival Case of Study - BAYDENİZ, Erdem and Kılıcı, Leyla (International Journal of Contemporary Economics and Administrative Sciences, 2023)
This study aims to determine the effect of locavorism on behaviour intention in the context of Goal-Oriented Behaviour Theory. The research population consists of tourists participating in the Alaçatı Herb Festival in İzmir province, and the survey technique was used to obtain the data by purposive sampling. The questionnaires were collected face-to-face between 24-28 March 2022, and 445 questionnaires were subjected to analysis. In the research, SmartPLS statistical software was used to test the hypotheses for the Goal-Oriented Behaviour Model, and locavorism scales and the structural equation model were used to analyse the data. In this context, according to the tourists participating in the research, it was determined that only negative anticipated emotions among the variables in the Goal-Oriented Behaviour Model did not affect desire, and all other variables affected the model. In addition, it was determined that lionisation and opposition from the dimensions of the locavorism variable affected behaviour, but communalization did not have an effect. Suggestions were developed in line with the results of the study.